The Effect of Capital Expenditure and Balancing Funds on Economic Growth in the Former Besuki Residency Area with locally-generated revenue as an Intervening Variable - Novi Aulia Ramadhani; Arief Bachtiar (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study examines the impact of capital expenditure, balancing funds, and local revenue on economic growth in the former Besuki Residency area, covering Banyuwangi, Jember, Situbondo, and Bondowoso Regencies during the 2014-2024 period. Using path analysis on panel data and individual district analysis, the study investigates the direct, indirect, and mediating effects of local revenue as an intervening variable. The results show that all three independent variables significantly affect economic growth in the panel data for all four regencies. Capital expenditure has a significant direct effect only in Bondowoso Regency and overall panel data, but is insignificant in Banyuwangi, Jember, and Situbondo. Balancing funds exhibit a significant direct effect across all regions, while local revenue has a consistent direct effect in all regions and panel data. The mediating role of local revenue is inconsistent, with the indirect effect of capital expenditure through local revenue being insignificant in all regions. On the other hand, the indirect effect of balancing funds through local revenue is significant in Banyuwangi, nearly significant in Jember and Situbondo, and insignificant in Bondowoso. These findings highlight the complexity of fiscal dynamics in decentralization, where local revenue management and governance factors are crucial. The study supports previous research suggesting that central fiscal transfers are less effective without strong local revenue support. Local governments are encouraged to enhance local revenue autonomy to maximize the multiplier effect of capital expenditures and balancing funds, fostering sustainable economic growth.